Three-Year Gait and Axial Outcomes of Bilateral STN and GPi Parkinson’s Disease Deep Brain Stimulation - Mei, Shanshan; Eisinger, Robert S.; Hu, Wei; Tsuboi, Takashi; Foote, Kelly D.; Hass, Christopher J.; Okun, Michael S.; Chan, Piu; Ramirez-Zamora, Adolfo (Frontiers in Human Neuroscience, 2020)
Objective: To examine the short- and long-term clinical outcomes of bilateral subthalamic nucleus (STN) and globus pallidus internus (GPi) deep brain stimulation (DBS) on gait and axial symptoms in Parkinson’s disease (PD) patients. Available data has been inconsistent and mostly short-term regarding the effect of both brain targets on gait and axial symptoms. We aimed to identify potential target specific differences at three-year follow-up from a large single center experience. Methods: We retrospectively reviewed short-term (6-month follow-up) and long-term (36-month follow-up) changes in the Unified Parkinson’s Disease Rating Scale (UPDRS) Part II and III total scores of 72 PD patients (53 with bilateral STN-DBS and 19 with bilateral GPi-DBS). An interdisciplinary team made the target specific decisions for each DBS patient. We analyzed changes in gait and axial subscores derived from UPDRS II and III. Results: In both the STN- and GPi-DBS cohorts, we observed no significant differences in gait and axial UPDRS derived subscores in the off-med/on stimulation state at long-term follow-up when compared to baseline. On-med axial scores remained similar in the short-term but worsened in both groups (STN, 2.23 ± 3.43, p < 0.001; GPi, 2.53 ± 2.37, p < 0.01) in the long-term possibly due to disease progression. At long-term follow-up, the UPDRS III off-med/on stimulation scores worsened but were persistently improved from baseline in both groups (-9.07 ± 13.9, p < 0.00). Conclusions: The study showed that long-term both STN- and GPi-DBS had a similar effect on gait and axial symptoms in UPDRS derived subscores at 36-month follow-up despite potential baseline differences in criteria for selection of each target. More sophisticated measures of gait and balance beyond the categorical UPDRS score will be needed for future studies.